2005
DOI: 10.1097/01.mat.0000161940.30190.6d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Fragility Calibration of Red Blood Cells

Abstract: Mechanical fragility of red blood cells (RBCs) is a critical variable for the hemolysis testing of many important clinical devices, such as pumps, valves, and cannulae, and gas exchange devices. Unfortunately, no standardized test for RBC mechanical fragility is currently well accepted. Although many test devices have been proposed for the study of mechanical fragility of RBCs, no one has ever shown that their results have any relevance to a blood pump. Therefore, the fundamental objective of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The deleterious effects of blood pumps, cardiac valves, and even needles on erythrocytes are well characterized. The cell damage is known to be a function of several parameters, among them shear stress, exposure time, blood contact material, and blood composition (14 ). For a cannula it has been shown that most of the hemolysis is produced on the external edge of the tip of the cannula, as the blood makes a 180-degree turn (15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The deleterious effects of blood pumps, cardiac valves, and even needles on erythrocytes are well characterized. The cell damage is known to be a function of several parameters, among them shear stress, exposure time, blood contact material, and blood composition (14 ). For a cannula it has been shown that most of the hemolysis is produced on the external edge of the tip of the cannula, as the blood makes a 180-degree turn (15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The flow velocity used in this study was 0.02 m s −1 , which was limited by the shutter time of the camera. When the channel width was smaller than 10 μm, the highest shear stress increased significantly to 300 Pa, sufficiently high for causing RBC lysis 21,22 . When the channel width was larger than 14 μm, the shear stress was not sufficient to bend the RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…However, RBC deflection increased linearly only when the flow velocity was lower than 0.06 m s −1 , after which nonlinearity occurred. This is because the stress induced by a flow velocity higher than 0.06 m s −1 exceeds RBC's yield stress (250 Pa to 300 Pa) 21,22,28 . Thus, a flow velocity o0.03 m s −1 was used in the experiments and was not considered to be sufficiently high enough to induce nonlinearity in the RBC effective stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…K 50 is the slope at this point. For all 6 units tested, quadraticallyinterpolated S 50 and corresponding K 50 values are listed in Table 1; the data also suggest some potential independence between these two values. While such characteristics permit straightforward comparisons, more complex profiles may reveal more meaningful patterns in stress susceptibilities.…”
Section: Figurementioning
confidence: 99%
“…Regarding mechanical fragility, one limitation on its adoptability for standardized clinical applications appears to have been a lack of a testing means that is both highly sensitive and clinically practical (50). However, we believe this erythrocyte property to be a particularly likely measure of membrane state to correlate with transfusion efficacy: Mechanical fragility represents a sample's propensity for hemolysis under sustained and varied physical stressesoffering greater potential, with proper configuration, to resemble the physiological stresses cells experience in vivo.…”
Section: Researching Candidate Metric(s)mentioning
confidence: 99%